MRPL44 regulates lipid metabolism in metabolic dysfunction-associated steatotic liver disease through BNIP3-mediated mitophagy - Liu, Siqi; Xiao, Lianggui; Cheng, Qiuchen; Liao, Qichao; Huang, Yuxin; Li, Xiangling; Zhang, Zhiwang; Xiao, Yang; Luo, Zupeng; Pan, Tingli; Sun, Yu; Sun, Chang; et al. (Frontiers in Nutrition, 2025)
ObjectiveMitophagy is a critical defense mechanism against metabolic dysfunction–associated steatotic liver disease. MRPL44, a mitochondrial ribosomal protein that regulates mitochondrial DNA-encoded gene expression, has not previously been linked to lipid metabolism.MethodsThis study employed an oleic acid/palmitic acid induced HepG2 cell models and a high-fat diet fed mouse models, combined with lentivirus-mediated MRPL44 overexpression and mitophagy assays, to investigate the regulatory role of MRPL44 in the progression of metabolic dysfunction–associated steatotic liver disease.ResultsOur findings demonstrated that MRPL44 alleviates lipid metabolic disorders induced by high-fat diet through the mitophagy pathway. Specifically, in oleic acid/palmitic acid-stimulated HepG2 cells, overexpression of MRPL44 reduced intracellular triglyceride accumulation and enhanced fatty acid oxidation. Moreover, liver-specific overexpression of MRPL44 in mice attenuated high-fat diet induced hepatic lipid deposition. Mechanistically, MRPL44 activated the BNIP3-dependent mitophagy pathway, promoted mitochondrial biogenesis, and mitigated mitochondrial damage, ultimately reducing lipid accumulation in hepatocytes.ConclusionThis study identifies MRPL44 as a novel regulator of lipid metabolism and a potential therapeutic target for metabolic dysfunction–associated steatotic liver disease.